Prometheus & Atlas by Jason Reza Jorjani - Mishlove, Jeffrey (Journal of Scientific Exploration, 2017)
Prometheus & Atlas by Jason Reza Jorjani. Arktos Media, 2016. 468 pp. 36.59 (paperback). ISBN 978-1910524619. A few years ago, I received a manuscript for Prometheus and Atlas from Jason Reza Jorjani, who had then recently received his doctoral degree in philosophy from NYU. Jorjani particularly wanted me to review his treatment of my book, The PK Man, in his final chapter. I was happy to do so; for while The PK Man has generally received many positive reviews, it was rare that another scholar would endeavor to incorporate my decade-long, field research project into their own body of work.